Data reduction techniques for Very Long Baseline Interferometric spectropolarimetry - Kemball, Athol James (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1993)
This thesis reports the results of an investigation into techniques for the calibration and imaging of spectral line polarization observations in Very Long Baseline Interferometry (VLBI). A review is given of the instrumental and propagation effects which need to be removed in the course of calibrating such obervations, with particular reference to their polarization dependence. The removal of amplitude and phase errors and the determination of the instrumental feed response is described. The polarization imaging of such data is discussed with particular reference to the case of poorly sampled cross-polarization data. The software implementation of the algorithms within the Astronomical Image Processing System (AlPS) is discussed and the specific case of spectral line polarization reduction for data observed using the MK3 VLBI system is considered in detail. VLBI observations at two separate epochs of the 1612 MHz OH masers towards the source IRC+ 10420 are reduced as part of this work. Spectral line polarization maps of the source structure are presented, including a discussion of source morphology and variability. The source is sigmficantly circularly polarized at VLBI resolution, but does not display appreciable linear polarization. A proper motion study of the circumstellar envelope is presented, which supports an ellipsoidal kinematic model with anisotropic radial outflow. Kinematic modelling of the measured proper motions suggests a distance to the source of ~ 3 kpc. The cirumstellar magnetic field strength in the masing regions is determined as 1-3 mG, assuming Zeeman splitting as the polarization mechanism.
Keywords: Very long baseline interferometry; Radio interferometers; Data reduction -- Research